2015
DOI: 10.5194/bg-12-5339-2015
|View full text |Cite
|
Sign up to set email alerts
|

Responses of leaf traits to climatic gradients: adaptive variation versus compositional shifts

Abstract: Abstract. Dynamic global vegetation models (DGVMs) typically rely on plant functional types (PFTs), which are assigned distinct environmental tolerances and replace one another progressively along environmental gradients. Fixed values of traits are assigned to each PFT; modelled trait variation along gradients is thus driven by PFT replacement. But empirical studies have revealed "universal" scaling relationships (quantitative trait variations with climate that are similar within and between species, PFTs and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 72 publications
(90 reference statements)
5
57
1
Order By: Relevance
“…There was no significant difference in the LMM slopes among different plant life‐forms (Table ), and similar results have been found between other chemical traits and climate gradients (e.g., Meng et al, ). These results suggest that the response of foliar pH to the geographical and environmental factors was nearly consistent for woody plants and herbs.…”
Section: Discussionsupporting
confidence: 85%
“…There was no significant difference in the LMM slopes among different plant life‐forms (Table ), and similar results have been found between other chemical traits and climate gradients (e.g., Meng et al, ). These results suggest that the response of foliar pH to the geographical and environmental factors was nearly consistent for woody plants and herbs.…”
Section: Discussionsupporting
confidence: 85%
“…As Kong and Henry () demonstrated that prior exposure to freezing stress enhanced Poa pratensis drought survival, some trait values are likely to benefit tolerance to both types of dehydration stresses. Our results showed that Mediterranean populations, which expressed summer dormancy, always had narrower leaves than other origins of D. glomerata , together with a high leaf dry matter content, that is traits values that have been previously mentioned as drought‐adaptive (Bartlett, Scoffoni, & Sack, ; Meng et al., ). Consistently, Mediterranean populations had higher summer drought survival, but this set of leaf traits was not associated with frost tolerance.…”
Section: Discussionsupporting
confidence: 73%
“…Considered from the broadest functional perspective, the range of values we observed for F v '/F m ' in a single genus and constant environment (0.37–0.57) fall well within the range observed at a continental scale and across multiple vegetation types (0.14–0.89) [65]. More narrowly, compared to diploid parents species, the allotetraploids we examined had increased trait ranges that were largely caused by increased maximum trait values, despite relatively low rates of photosystem II gene retention following polyploidy in Glycine , Medicago , and Arabidopsis [66].…”
Section: Discussionsupporting
confidence: 73%